The governing system of the Vatican City State under the Fundamental Law of the Vatican City State of 2023 - Agnieszka Romanko (Journal of Modern Science)
Objectives This article aims at characterising the current Fundamental Law ("constitution") of the Vatican City State with particular attention given to the amendments introduced by Pope Francis in 2023. The article will attempt to answer the following questions: What was the reason for the reform of the Vatican City State? What is the structure of the Vatican City State? What distinguishes the Vatican City State from other states?